The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/nu12040929
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxyvitamin D, 1,25-Dihydroxyvitamin D, and Peripheral Bone Densitometry in Adults with Celiac Disease

Abstract: Background: Adults with celiac disease (CeD) show low bone mineral density (BMD) and high fracture risk. CeD guidelines suggest measurements of serum minerals and vitamin D. However, studies on vitamin levels in CeD patients are contradictory. Aim: To investigate in CeD, 25-hydroxy-vitamin D [25(OH)D], 1,25-dihydroxy-vitamin D [1,25(OH)2D], and related analytes and to evaluate their relationships to peripheral BMD as assessed by peripheral quantitative computed tomography (pQCT). Methods: Gluten-free diet (GFD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…This has led to the hypothesis that vitamin D deficiency in early life may predispose to celiac disease due to seasonal differences in UVB exposure and subsequent 25(OH)D concentrations or via dysregulation of the immune response leading to an abnormal intestinal mucosa with increasing permeability ( 21 , 22 ). Although low 25(OH)D concentrations have been reported at the time of celiac disease diagnosis ( 23 26 ), this can be attributed to deranged dietary absorption from a damaged gut epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to the hypothesis that vitamin D deficiency in early life may predispose to celiac disease due to seasonal differences in UVB exposure and subsequent 25(OH)D concentrations or via dysregulation of the immune response leading to an abnormal intestinal mucosa with increasing permeability ( 21 , 22 ). Although low 25(OH)D concentrations have been reported at the time of celiac disease diagnosis ( 23 26 ), this can be attributed to deranged dietary absorption from a damaged gut epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that GFD may restore skeletal defects, particularly in children ( Figure 2 ), thus decreasing the risk of fracture in patients with celiac disease [ 78 , 79 , 80 , 81 , 82 , 83 ]. Generally, from a clinical point of view, after starting GFD, systemic inflammation decreases, the intestinal mucosa heals progressively, and normal gastrointestinal absorption is re-established.…”
Section: Celiac Diseasementioning
confidence: 99%
“…Generally, from a clinical point of view, after starting GFD, systemic inflammation decreases, the intestinal mucosa heals progressively, and normal gastrointestinal absorption is re-established. Consequently, bone resorption decreases, in part explaining the increase in BMD [ 83 ] and, ultimately, the decrease in fracture risk. Moreover, celiac disease patients on GFD undergo a significant decrease in the parathyroid hormone (PTH) levels, together with a significant increase in the calcium and vitamin D concentrations, thus allowing adequate skeletal mineralization.…”
Section: Celiac Diseasementioning
confidence: 99%
“…The antitissue transglutaminase (anti-tTG) antibody is a key criterion for establishing the diagnosis of celiac disease and monitoring the adherence to a gluten-free diet (GFD) (1). The presence of anti-tTG autoantibodies is associated with small bowel mucosal damage, whereas celiac serology normalization is associated with mucosal healing and improvement in metabolic outcomes such as anemia and bone density (11,12). Celiac autoimmunity has been associated with other comorbidities and subsequent poor health outcomes, aside from small intestinal inflammation.…”
Section: Introductionmentioning
confidence: 99%